EFEKTIFITAS PEMASANGAN KAPASITOR SEBAGAI METODE ALTERNATIF PENGHEMAT ENERGI LISTRIK - M. Tony Prasetyo; Luqman Assaffat (MEDIA ELEKTRIKA, 2010)
Efficiency needs to be done by PLN as a provider of electrical energy and of course also by the user community as consumers of electrical energy. One of the efficiency measures to conserve energy use in the community is the use of energy-efficient electical appliances (energy saver) areused both in business, commercial or industrial or domestic sector. Energy-efficient appliances are now widely sold in the wider community as they seek to offset the cost of electrical energy consumption. Equipment generally contains capacitor banks or elco (electrolyt condensator) whichcan reduce electric currents, but no significant effect on consumer savings account payments.The Study that's obout improving the power factor has been more on the side of the electricity supplier. both in transmission and distribution. On the load side (electricity consumers), the measurement of power factor and load balancing only on the main panel or distribution ponel.so that the measured accumulated loads of different types of loads.So far research on increasing the load power factor only produces the resulting level of power efficiency and whether this level can still be expected usefulness in relieving the financial burden of the electricity customer bills or not. So we need to do a study b determine the efficiencyof the dominant power generated by the load in conjunction with electric power triangle.Keywords : Power Capacitor, Load, efficiency of electric power